الساركوئيد والوشم التجميلي - حسن فوز (Latakia University Journal -Medical Sciences Series, 2019)
إن حدوث آفات حبيبومية في أماكن الوشوم، معروف الحدوث عند مرضى الساركوئيد، وهو يميز بموجوداته النسيجية النوعية للساركوئيد، ولكن إذا كان لا يوجد في قصة المرضى أي مرض ساركوئيدي سابق لظهور الاندفاعات على الوشم، هل يمكن للوشم أن يكشف داء الساركوئيد المستبطن؟ المشاهدات السريرية: نقدم في هذا العرض ثلاث مريضات ليس لديهن أية سوابق مرضية للساركوئيد الجهازي أو الجلدي، طورن ظهور آفات حطاطية خطية مصطفة على مسير حواجبهن، ظهرت هذه الآفات بعد فترة زمنية تتراوح بيت عدة أشهر إلى عدة سنوات بعد إجراء الوشوم عليها، كشف الفحص النسيجي فيها وجود تشكلات حبيبومية ساركوئيدية الشكل، كما كشف التصوير الشعاعي للرئتين وجود ضخامات منصفية لدى سيديتين منهما. الخلاصة: تظهر هذه الحالات الثلاث حدوث تفاعل فريد بعد إجراء الوشم التجميلي، وهو التفاعل الساركوئيدي، ويؤيد مفهوم أن الوشم التجميلي يمكن أن يكون كاشفاً للساركوئيد الجهازي المستبطن Background: The development of granulomatous lesions within tattoos is a well-recognized occurrence in individuals with sarcoidosis. The characteristic histopathological finding of sarcoidosis is the presence of noncaseating granulomas; but if patients have no history of sarcoidosis prior to their tattoos, is there any role of tattoo to reveal underlying sarsoidosis? Observations: We describe three patients who had multiple linearly arranged papules along their eyebrows. They had had cosmetic tattooing performed on these areas several months to several years prior to presentation. Histopathologic examination revealed sarcoidal granulomas. Hilar adenopathy was noted on a chest radiograph in two patients. Conclusions: These cases demonstrate a unique adverse result after cosmetic tattooing and highlights the concept that tattoo may reveal underlying systemic sarcoidosis. In this setting, further investigation for the relation between tattoo and systemic sarcoidosis is recommended.